Sodium MRI in Pediatric Brain Tumors - Bhatia, Aashim; Kline, Cassie; Madsen, Peter J.; Fisher, Michael J.; Boada, Fernando E.; Roberts, Timothy P.L. (American Journal of Neuroradiology, 2025)
Direct sodium MRI (23Na-MRI) derives its signal from spin-manipulation of the 23Na nucleus itself and not the more conventional and familiar 1H-MRI. Although present at much lower concentrations in the human body than the 1H nuclei in the water molecule H2O, advances in coil design and pulse sequence development have enabled the feasibility of human in vivo 23Na-MRI. Additionally, 23Na-MRI has the potential to offer nuanced physiologic insights not available to conventional MRI; this feature forms the basis of interest in its development and optimism for its novel clinical utility. 23Na-MRI has the potential to be a useful noninvasive imaging technique to assess biochemical and physiologic cellular changes in tissues, eg, cell integrity and tissue viability. Pathologically, the concentration of total sodium is elevated in tumors relative to normal counterparts due to increased intracellular sodium and/or an increased proportion of extracellular space (reflecting changes in cell morphology and anomalies of homeostasis). Here we review the technological advancements with improved pulse sequences and reconstruction methods that counter the inherent challenges of measuring sodium concentrations in the pediatric brain (in particular, its short-tissue T2 value) and present detailed imaging approaches to quantifying sodium concentrations in the pediatric brain that can be assessed in various CNS pathologies, with the focus on pediatric brain tumors.BSCbound sodium concentrationIBRiterative Bowsher reconstructionIRinversion recoveryISCintracellular sodium concentration23Na-MRIsodium MRIRFradiofrequencyTPItwisted projection imagingTSCtotal sodium concentration